A comprehensive molecular approach to the detection of drug-type versus fiber-type hemp varieties. (May 2021) - Forlani, Giuseppe; Petrollino, Davide
Highlights: Fast and easy methods to discriminate hemp from marijuana are highly desirable. Industrial hemp differs from marijuana for low tetrahydrocannabinol content. Reliable cannabinoid analysis is possible with flowers, but not with seeds and leaves. Cannabinoid acid synthases from the two chemotypes seem to have different features. Molecular markers would allow distinguishing drug-type from fiber-type hemp varieties. Abstract: The availability of molecular markers able to distinguish drug-type from fiber-type Cannabis sativa cultivars would allow fast and cheap analysis of any plant specimen, including seeds and leaves. Several approaches to this issue have been described, mainly using polymorphisms in the genes coding for tetrahydrocannabinol acid synthase or cannabidiolic acid synthase. Some studies reported sequencing of these genes from small groups of hemp varieties belonging to both chemotypes, showing the occurrence of specific DNA signatures. However, the effectiveness of the corresponding primers to discriminate among chemotypes has been validated on a limited number of cultivars, or not tested at all. Here we report a thorough in silico analysis of available gene sequences for both synthases, showing the existence of hypervariable regions at 3' and 5' ends. This notwithstanding, some possible signatures were identified, and 12 putatively specific primer pairs were designed and tested on 16 fiber-type and 11 drug-type varieties. In most cases inconsistent results were obtained, further strengthening the high genetic variability of these genes in hemp germplasm, yet some highly informative polymorphisms were identified. Potentiality and perspectives of this approach are discussed.